A Qualitative Study of Perception of School Safety among Youth in a High Crime City. (2nd July 2020) - Cobbina, Jennifer E.; Galasso, Matthew; Cunningham, Mary; Melde, Chris; Heinze, Justin
ABSTRACT: School safety is a key feature of the learning environment. Research suggests if students perceive their environment as unsafe they will face a myriad of possible detrimental consequences. Using qualitative interviews, we explore the factors most consistently identified by students as important in their feelings of safety. We examine whether the type of building (elementary vs. high school) impacts the themes generated by students in their responses about feelings of safety in their school. Our results speak to how perceptions of school safety are formed, how students understand the role of other students and adults in mitigating or exacerbating violence, as well as the role external resources in their environments play in protecting youth from school violence.